Transport of Corilagin, Gallic Acid, and Ellagic Acid from Fructus Phyllanthi Tannin Fraction in Caco-2 Cell Monolayers. (21st September 2016) - Mao, Xin; Wu, Ling-Fang; Zhao, Hai-juan; Liang, Wen-Yi; Chen, Wen-Jing; Han, Shu-Xian; Qi, Qi; Cui, Ya-Ping; Li, Shi; Yang, Guang-Hui; Shao, Yan-Yan; Zhu, Dan; et al.
Abstract : Objective . To investigate the absorption property of the representative hydrolyzable tannin, namely corilagin, and its hydrolysates gallic acid (GA) and ellagic acid (EA) from the Fructus Phyllanthi tannin fraction (PTF) in vitro . Methods . Caco-2 cells monolayer model was established. Influences of PTF on Caco-2 cells viability were detected with MTT assay. The transport across monolayers was examined for different time points, concentrations, and secretory directions. The inhibitors of P-glycoprotein (P-gp), multidrug resistance proteins (MRPs), organic anion transporting polypeptide (OATP) and sodium/glucose cotransporter 1 (SGLT1), and tight junction modulators were used to study the transport mechanism. LC-MS method was employed to quantify the absorption concentration. Results . The apparent permeability coefficient( P a p p ) values of the three compounds were below 1.0 × 10 −6  cm/s. The absorption of corilagin and GA were much lower than their efflux, and the uptake of both compounds was increased in the presence of inhibitors of P-gp and MRPs. The absorption of EA was decreased in the company of OATP and SGLT1 inhibitors. Moreover, the transport of corilagin, GA, and EA was enhanced by tight junction modulators. Conclusion . These observations indicated that the three compounds in PTF were transported via passive diffusion combined with protein mediated transport. P-gp and MRPs might get involved in the transport of corilagin and GA. The absorption of EA could be attributed to OATP and SGLT1 protein.